Evaluation of Oncology Hospital at Home: Unplanned Health Care Utilization and Costs in the Huntsman at Home Real-World Trial. Issue 23 (10th August 2021) - Mooney, Kathi; Titchener, Karen; Haaland, Benjamin; Coombs, Lorinda A.; O'Neil, Brock; Nelson, Richard; McPherson, Jordan P.; Kirchhoff, Anne C.; Beck, Anna C.; Ward, John H.
Abstract : PURPOSE: Patients with cancer experience high rates of morbidity and unplanned health care utilization and may benefit from new models of care. We evaluated an adult oncology hospital at home program's rate of unplanned hospitalizations and health care costs and secondarily, emergency department (ED) use, length of hospital stays, and intensive care unit (ICU) admissions during the 30 days after enrollment. METHODS: We conducted a prospective, nonrandomized, real-world cohort comparison of 367 hospitalized patients with cancer—169 patients consecutively admitted after hospital discharge to Huntsman at Home (HH), a hospital-at-home program, compared with 198 usual care patients concurrently identified at hospital discharge. All patients met clinical criteria for HH admission, but those in usual care lived outside the HH service area. Primary outcomes were the number of unplanned hospitalizations and costs during the 30 days after enrollment. Secondary outcomes included length of hospital stays, ICU admissions, and ED visits during the 30 days after enrollment. RESULTS: Groups were comparable except that more women received HH care. In propensity-weighted analyses, the odds of unplanned hospitalizations was reduced in the HH group by 55% (odds ratio, 0.45, 95% CI, 0.29 to 0.70; P < .001) and health care costs were 47% lower (mean cost ratio, 0.53; 95% CI, 0.39 to 0.72; P < .001) over the 30-day period. Secondary outcomes also favored HH. Total hospital stay days were reduced by 1.1 days ( P = .004) and ED visits were reduced by 45% (odds ratio, 0.55; 95% CI, 0.33 to 0.92; P = .022). There was no evidence of a difference in ICU admissions ( P = .972). CONCLUSION: This oncology hospital at home program shows initial promise as a model for oncology care that may lower unplanned health care utilization and health care costs.